2005
DOI: 10.1002/jcb.20404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of potential protective effects of melatonin, indole‐3‐propionic acid, and propylthiouracil against lipid peroxidation caused by potassium bromate in the thyroid gland

Abstract: Potassium bromate (KBrO3) is a prooxidant and carcinogen, inducing thyroid tumors. Melatonin and indole-3-propionic acid (IPA) are effective antioxidants. Some antioxidative effects of propylthiouracil (PTU)--a thyrostatic drug--have been found. The aim of the study was to compare protective effects of melatonin, IPA, and PTU against lipid peroxidation in the thyroids, collected from rats treated with KBrO3, and in homogenates of porcine thyroids, incubated in the presence of KBrO3. Wistar rats were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
(32 reference statements)
5
28
0
Order By: Relevance
“…It is well known (from many in vivo and in vitro studies) that melatonin is a perfect antioxidant because of its effective protective action against damaging effects of different prooxidants and the fact that under basal conditions it does not change the level of oxidative damage to macromolecules [12,13,31,32]. The observation – made by us in the present study – of the decreasing effect of CAPE on the basal LPO level, was unexpected and also undesirable.…”
Section: Discussionsupporting
confidence: 42%
“…It is well known (from many in vivo and in vitro studies) that melatonin is a perfect antioxidant because of its effective protective action against damaging effects of different prooxidants and the fact that under basal conditions it does not change the level of oxidative damage to macromolecules [12,13,31,32]. The observation – made by us in the present study – of the decreasing effect of CAPE on the basal LPO level, was unexpected and also undesirable.…”
Section: Discussionsupporting
confidence: 42%
“…35 Co-treatment with Mel prevented the KBrO 3 -induced oxidative damage to lipids in rat kidney and in blood serum, 36 as well as in rat thyroid gland. 37 Pretreatment with Mel likewise reduced indomethacin-induced gastric damage and plasma malondialdehyde level in rats. 38 The protective effects of Mel, observed both in our study and in the studies cited above, could have been due to its ability to scavenge numerous toxic species, such as hydroxyl radical ( OH), peroxynitrite anion (ONOO À ) or nitric oxide (NO ).…”
Section: Resultsmentioning
confidence: 96%
“…IPA acts as an endogenous electron donor primarily by detoxifying reactive oxygen species. This mechanism could be responsible for the high efficacy of antioxidative action of IPA in vivo like MLT [82]. It was found that indole derivatives that do not contain the redox active hydroxyl group at position 5 of the indole ring do not act as chain breaking antioxidants and therefore are either poorly protective or not effective in vitro.…”
Section: -Lohmentioning
confidence: 96%